PENGARUH PERBANDINGAN KENTANG KUKUS DAN TEPUNG KACANG HIJAU (Phaseolus radiatus L.) TERHADAP KARAKTERISTIK FLAKES - Nindyawati, Lina; Ina, Putu Timur; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This study aims to determine the effect of steamed potatoes and green bean flour on the characteristics of flakes, and to know the right ratio of steamed potatoes and green bean flour which produced flakes with the best characteristics. The was used in this research completely randomized design with the treatment ratio of steamed potatoes and green bean flour, which consists of 6 levels such as: 35% : 65%, 40% : 60%, 45% : 55%, 50% : 50%, 55% : 45%, 60% : 40%. The treatment was repeated 3 times to obtained 18 units of the experiment. The data were analysed by variance analysis  and if the treatment had an effect on the variable then continued with Duncan test. The result showed steamed potatoes and green bean flour ratio had a significant effect on water content, ash content, fat content, protein content, carbohydrate content, color (hedonic), aroma (hedonic), texture (hedonic and scoring), taste (hedonic) and overall acceptance (hedonic). Ratio of 35% steamed potatoes and 65% green bean flour produced flakes with the best characteristics, with 2.41 % water content, 4.57 % ash content, 19.16% protein content, 10.20% fat content, 63.66% carbohydrate content, color liked, aroma liked, texture crunchy and liked, taste netral and overall acceptance rather liked.